P791 Assessment of urethritis etiology among HIV-infected men attending an STI clinic in lilongwe, malawi. (14th July 2019) - Matoga, Mitch; Chen, Jane; Massa, Cecilia; Ndalama, Beatrice; Mathiya, Esther; Bonongwe, Naomi; Kamtambe, Blessings; Jere, Edward; Kamanga, Edith; Tegha, Gerald; Chikaonda, Tarsizio; Cohen, Myron; et al.
Abstract : Background: Malawi uses syndromic management for the treatment of sexually transmitted infections (STIs). However, the etiology profile of STIs has been shown to change over time. We conducted a current assessment for etiology of urethral discharge (UD) among men in Lilongwe Malawi to inform development of effective national treatment guidelines. Methods: We enrolled a cohort of HIV infected men with UD who were either ART naïve or on ART for ≥12 weeks at Bwaila STI clinic. We collected blood samples and urethral swabs for STI etiologic testing as follows: Neisseria gonorrhoeae (GeneXpert, culture), Chlamydia trachomatis (GeneXpert), and Trichomonas vaginalis (OSOM – Trichomonas Rapid Test). All patients were treated syndromically with gentamicin, doxycycline, and metronidazole, per Malawian standard of care. Clinical and demographic characteristics were also collected. We assessed differences between men on ART for ≥12 weeks and men not on ART using chi square tests and exact statistics (alpha=0.05). Results: 189 men were enrolled between January 1, 2017 and December 31, 2018; 87 (46.0%) were not on ART, and 102 (54.0%) were on ART. Participants reported urethral discharge for a median of 4 days (IQR: 3, 7). Among participants, 152 (80.4%) tested positive for gonorrhea via GeneXpert and 124 (66.7%) via culture; 17 (9.0%) tested positive for chlamydia, 6 (3.2%) tested positive for trichomonas and 30 (15.9%) did not test positive for any of the three etiologies. 15 (7.9%) participants had multiple STIs. There were no differences in distribution of etiologies (individual or multiple) between men on and not on ART (p≥0.10 for all comparisons). Conclusion: The overwhelming etiology of urethritis among HIV-infected men in Malawi is Neisseria gonorrhoeae . Current syndromic management guidelines that treat gonorrhea, chlamydia and trichomonas seem adequate for treatment of UD but future guidelines must be informed by ongoing monitoring of antibiotic resistance. Disclosure: No significant relationships.